(untitled) (Sciences & Technology. A, exactes sciences, 2013)
The study of 3-methylphenol (m-cresol) photodegradation has been achieved in two system, UV / Fe(III)-Cit and UV / Fe(III)-Cit / H2O2 in natural (pH = 6.5). The presence of H2O2 in UV / Fe(III)-Cit system reduce the efficiency of m-cresol degradation at low concentration, however for the high level of H2O2 the process is improved. The optimal concentration of H2O2 was found to be 5 mM. This can be probably explained by a low Fe(II) formation of in this system. The result shows in the both systems that the acidic media is favorable for this kind of reaction. The Comparison between the aquacomplexes and Fe(III)-Cit complex in the presence or absence of H2O2 have confirmed that the best condition of m-cresol degradation was achieved with the addition of H2O2. Additionally, the use of 1.0 % of tertiobutanol as a scavenger confirmed the intervention of hydroxyl radicals in the m-cresol photodegradation.